2020
DOI: 10.1016/j.cell.2020.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Diet Diurnally Regulates Small Intestinal Microbiome-Epithelial-Immune Homeostasis and Enteritis

Abstract: Throughout a 24-h period, the small intestine (SI) is exposed to diurnally varying food-and microbiomederived antigenic burdens but maintains a strict immune homeostasis, which when perturbed in genetically susceptible individuals, may lead to Crohn disease. Herein, we demonstrate that dietary content and rhythmicity regulate the diurnally shifting SI epithelial cell (SIEC) transcriptional landscape through modulation of the SI microbiome. We exemplify this concept with SIEC major histocompatibility complex (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
109
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(130 citation statements)
references
References 73 publications
12
109
0
Order By: Relevance
“…Gut microbiota plays an important role in the regulation of AP-related gene expression and altered microbiota–epithelium communication resulting in impaired immune and neural signaling and gut pathophysiology associated with many chronic diseases, including graft-versus-host and Crohn’s disease [ 20 , 21 ]. Our previously published data on microbial communities in WKY and SHR had identified the enrichment of five bacterial taxa ( Allobaculum , Bacteroides , Bifdobacterium , Blautia and Gordonibacter ) in WKY rat and one taxa ( Turicibacter) in the SHR microbiomes [ 1 ].…”
Section: Resultsmentioning
confidence: 99%
“…Gut microbiota plays an important role in the regulation of AP-related gene expression and altered microbiota–epithelium communication resulting in impaired immune and neural signaling and gut pathophysiology associated with many chronic diseases, including graft-versus-host and Crohn’s disease [ 20 , 21 ]. Our previously published data on microbial communities in WKY and SHR had identified the enrichment of five bacterial taxa ( Allobaculum , Bacteroides , Bifdobacterium , Blautia and Gordonibacter ) in WKY rat and one taxa ( Turicibacter) in the SHR microbiomes [ 1 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies investigating diurnal cycling of the gut microbiome have used samples collected under 24-h ( 9 , 11 , 13 ) and 48-h ( 10 , 12 , 63 ) conditions. Although in general, it is preferable to use 48-h data for circadian studies since it reduces type I errors, recent advances in bioinformatic tools, such as MetaCycle ( 35 ), allow rigorous analysis of 24-h circadian data.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that host circadian disruption can result in the dysbiosis of the gut (such as the large intestine) microbiota (Thaiss et al, 2014;Gao et al, 2019). Small intestinal microbes also have essential physiological effects on the host (Tuganbaev et al, 2020). Research has shown that the jejunum, as the middle third of the small intestine, contains a distinctive bacterial population that differs from that in the colon, which plays a major role in absorption of carbohydrates, amino acids, small peptides, and vitamins from nutritional sources (Sundin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%